Enhancement of polarization anisotropy in ultrafast carrier dynamics by intramolecular excitation in the organic conductor κ-(BEDT- TTF)2Cu(NCS)2. (1st December 2021) - Nakagawa, K.; Sato, T.; Tsuchiya, S.; Yamada, J.; Toda, Y.
Abstract: In this work, in order to investigate the origin of the anomalous polarization dynamics observed in the normal conducting state of the organic superconductor κ -(BEDT-TTF)2 Cu(NCS)2, we performed optical pump probe measurements by varying the probe pulse energy from to 1.59 eV. We found that the polarization-dependent transient signal was most enhanced at, which was close to the intramolecular excitation energy of the BEDT-TTF molecules but is not exactly matched. This difference is linked to the formation of an energy gap at the Fermi energy at low temperatures, which results in an increase or decrease in pump-induced absorption between the states near the Fermi energy and the intramolecular excited states depending on probe polarization. In other words, the intramolecular excitation at 1.41 eV, which has a strong polarization dependence, serves as a probe of the dynamics involved in gap formation. A simple calculation shows that the size of the gap is, which is close to that of the BEDT-TTF based Mott insulators. It is suggested that the gap arises from the phase-separated Mott state caused by photoinduced modulation of effective electron correlation.